2020
DOI: 10.3390/cancers12102913
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Mutations of MYD88 and CD79B in Diffuse Large B-Cell Lymphoma and Implications for Clinical Practice

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common non-Hodgkin’s lymphoma in adults. Despite the recognition of transcriptional subtypes with distinct functional characteristics, patient outcomes have not been substantially altered since the advent of chemoimmunotherapy (CIT) twenty years ago. Recently, a few pivotal studies added to the disease heterogeneity by describing several activating mutations, which have been associated with disease presentation, B-cell function and behavior, and final outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…Both cases had complete CDKN2A deletions, an alteration we have observed to be highly recurrent in VRL patients and which is a promising genomic biomarker with potential clinical utility that warrants further investigation [ 42 ]. MYD88 , a gene encoding for an NF-kB pathway component, is also recurrent in B-cell lymphomas [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] and was found here as a truncal activating mutation in Case 2. Interestingly, Case 1 harbored a MYD88 p.A221T mutation with a highly subclonal status in the brain tissue sample (8% variant fraction).…”
Section: Discussionmentioning
confidence: 86%
“…Both cases had complete CDKN2A deletions, an alteration we have observed to be highly recurrent in VRL patients and which is a promising genomic biomarker with potential clinical utility that warrants further investigation [ 42 ]. MYD88 , a gene encoding for an NF-kB pathway component, is also recurrent in B-cell lymphomas [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] and was found here as a truncal activating mutation in Case 2. Interestingly, Case 1 harbored a MYD88 p.A221T mutation with a highly subclonal status in the brain tissue sample (8% variant fraction).…”
Section: Discussionmentioning
confidence: 86%
“…For example, ibrutinib, a small-molecule drug that targets Bruton's tyrosine kinase (BTK), can be considered for the treatment of patients with VRL who have an underlying MYD88 L265P mutation, which is known to trigger lymphomagenesis via BTK activation. Although there is currently no clear correlation between MYD88 mutational profiles and ibrutinib response (Visco et al, 2020 ), several studies have shown clinical responses to ibrutinib treatment in some DLBCL patients with an MYD88 L265P mutation (Deng et al, 2017 ; Soussain et al, 2019 ). MYD88 L265P mutations frequently co-occur in DLBCL patients who also harbor a mutation of CD79B, a subunit that is important for transducing BCR signaling.…”
Section: Vitreoretinal Lymphoma (Vrl) Diagnostic Approachesmentioning
confidence: 99%
“…The hypersensitivity of MYD88/CD79B double-mutant DLBCLs to ibrutinib treatment is probably due to the co-inhibition of BTK and CD79B-dependent BCR signaling. Taken together, oncogenic mutations of MYD88 and CD79B in DLBCL have major implications for clinical practice (Visco et al, 2020 ) and may provide useful genetic tools for personalized targeted therapies.…”
Section: Vitreoretinal Lymphoma (Vrl) Diagnostic Approachesmentioning
confidence: 99%
“…For example, ibrutinib, a small-molecule drug that targets Bruton's tyrosine kinase (BTK), can be considered for the treatment of patients with VRL who have an underlying MYD88 L265P mutation, which is known to trigger lymphomagenesis via BTK activation. Although there is currently no clear correlation between MYD88 mutational profiles and ibrutinib response (Visco et al, 2020), several studies have shown clinical responses to ibrutinib treatment in some DLBCL patients with an MYD88 L265P mutation (Deng et al, 2017;Soussain et al, 2019). MYD88 L265P mutations frequently co-occur in DLBCL patients who also harbor a mutation of CD79B, a subunit that is important for transducing BCR signaling.…”
Section: Myeloid Differentiation Primary Response 88 (Myd88)mentioning
confidence: 99%
“…The hypersensitivity of MYD88/CD79B double-mutant DLBCLs to ibrutinib treatment is probably due to the co-inhibition of BTK and CD79B-dependent BCR signaling. Taken together, oncogenic mutations of MYD88 and CD79B in DLBCL have major implications for clinical practice (Visco et al, 2020) and may provide useful genetic tools for personalized targeted therapies.…”
Section: Myeloid Differentiation Primary Response 88 (Myd88)mentioning
confidence: 99%